2020
DOI: 10.1021/acs.macromol.9b02217
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Gel Point of Polymer Model Networks by Computer Simulations

Abstract: The gel point of end-linked model networks is determined from computer simulation data. It is shown that the difference between the true gel point conversion, p c , and the ideal mean field prediction for the gel point, p c,id , is a function of the average number of cross-links per pervaded volume of a network strand, P , and thus, contains an explicit dependence on junction functionality f . On the contrary, the amount of intra-molecular reactions at the gel point is independent of f in a first approximation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 109 publications
(416 reference statements)
8
73
0
Order By: Relevance
“…, in accordance with the result of numerical simulations [26]. A more rigorous description of this effect requires the inclusion of fluctuation corrections.…”
Section: Finite-size Loops Of Real Networksupporting
confidence: 86%
See 2 more Smart Citations
“…, in accordance with the result of numerical simulations [26]. A more rigorous description of this effect requires the inclusion of fluctuation corrections.…”
Section: Finite-size Loops Of Real Networksupporting
confidence: 86%
“…A similar effect was observed in numerical simulations of networks obtained near the gel point, which is an analog of the percolation transition in low-molecular-weight solids. It is shown that the elastic modulus of such networks vanishes at a finite density of the network monomers [26]. One can estimate the corresponding shift in critical conversion p cµ at which G = 0, compared with the gel point at the conversion p cγ , at which the average degree of polymerization of soluble molecules diverges.…”
Section: Finite-size Loops Of Real Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies exist, highlighting the heterogeneous character of the polymer network structure of vinylic hydrogels. [8][9][10] In this study, we build upon existing knowledge of this system by combining it with a focused analysis of the network architecture in relation to the bis-acrylamide (bis-AAm) cross-linker concentration. The distribution of the cross-linker in the polymer network is analyzed on both nanoscopic and microscopic scales by means of smallangle X-ray scattering (SAXS) and light transmittance.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical analysis of finite-z corrections for the bond thresholds has recently been given by Frei and Perkins [32]. Some related work on polymer systems has also appeared recently [33].…”
Section: Introductionmentioning
confidence: 99%